Chemical compatibility at the interface of garnet-type Ga-LLZO solid electrolyte and high-energy Li-rich layered oxide cathode for all-solid-state batteries - Natalia B. Timusheva; Alexander A. Golubnichiy; Anatolii V. Morozov; Arseniy S. Burov; Dmitry A. Aksyonov; Aleksandra A. Savina; Roman G. Markopolskii; Artem M. Abakumov (Scientific Reports, 2025)
Abstract All-solid-state batteries (ASSBs) with a garnet-type solid electrolyte have been considered promising alternatives to traditional batteries with a liquid organic electrolyte, due to their enhanced safety and ability to accommodate high energy density electrodes. In this study, we conducted a comprehensive investigation of the high-temperature chemical compatibility between the garnet-like Li6.4Ga0.2La3Zr2O12 (Ga-LLZO) electrolyte and high-energy-density Li-rich layered Li1.2Ni0.2Mn0.6O2 cathode (LNM). Our findings suggest that a high temperature reaction between the Li-rich cathode and Ga-LLZO occurs at 700-900oC depending on the form of reactants. This reaction results in the formation of La(Ni, Mn)O3 and Li2ZrO3 as the two main products, as confirmed by powder X-ray diffraction and transmission electron microscopy analysis. Li2ZrO3 was discovered for the first time as a reaction product, and its formation in the case of Li-rich layered cathode material was rationalized with DFT + U calculations. The results were also compared with those obtained for a typical layered high-energy-density cathode material LiNi0.8Mn0.1Co0.1O2 (NMC811).